Effect of indoor workplace smoking ban regulation on smoking behavior among occupational populations in China - Xinying ZENG; Xinbo DI; Yi NAN; Huiyu XIE; Zida MENG; Lin XIAO; Shiwei LIU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the impact of indoor workplace smoking ban regulation on smoking behavior among various occupation groups in different regions of China, and to provide a reference for evaluating and promoting smoke-free indoor workplaces. MethodsThe data on 5 795 persons working in indoor places were collected from the National Adult Tobacco Survey conducted in 2018 across China. Unconditional multivariate logistic regression analysis was adopted to analyze the effect of indoor workplace smoking ban regulation on smoking behavior among occupational groups. ResultsNon-comprehensive and comprehensive smoking prohibition in indoor workplace were reported by 3 153 (54.4%) and 2 642 (45.6%) of all the employed persons. Of the 3 153 employed persons working in indoor places without comprehensive smoking prohibition, 2 324 reported ever having seen someone (including themselves) smoking in workplace, with a weighted ratio of 75.9%; while of the 2 642 employed person working in indoor places with comprehensive smoking prohibition, 743 reported ever having seen someone smoking in workplace, with the weighted ratio of 27.3%. After adjusting for gender, age, occupation, living area (urban/rural), residence region (eastern/western), current smoking, attitude towards smoking prohibition in workplace, and awareness of health hazards associated with second-hand smoke, the results of logistic regression analysis showed that the employed persons working in indoor places without comprehensive smoking prohibition were less likely to have seen someone smoking in indoor workplace (odds ratio = 0.14, 95% confidence interval: 0.12 - 0.17). ConclusionComprehensive indoor workplace smoking prohibition could reduce indoor smoking among occupational persons.